An appraisal of the prevalence and attributes of traumatic dental injuries in the permanent anterior teeth among 7-14-Year-Old school children of North East Delhi - Kopal Garg; Namita Kalra; Rishi Tyagi; Amit Khatri; Gaurav Panwar (Wolters Kluwer Medknow Publications, 2017)
Aims: The aim of this study was to assess the prevalence, associated risk factors, characteristics, and pattern of traumatic dental injuries (TDIs) in the permanent anterior teeth among school children of North East Delhi area. Settings and Design: A cross-sectional study was done in 3000 school-going children aged 7-14 years. Materials and Methods: A detailed case history and clinical examination were performed on the entire sample population. TDIs were recorded according to Andreasen's epidemiological classification of TDIs including World Health Organization codes. Statistical Analysis Used: For finding the independent association of the significant variables with outcome, multivariable logistic regression analysis was used. Results: A prevalence of 10.7% was observed in the sample being studied. Dental trauma was significantly (P < 0.05) associated with male gender, and high statistical significance (P < 0.001) was noted with age, participation in sports, lip seal, and overjet. Fall of the child while playing by himself/herself was the most common cause; afternoon and schools were the most common time and place of occurrence of TDIs, respectively. Single tooth enamel fractures in the left maxillary central incisors were most commonly seen. Adhesive restorations were the most frequent form of treatment required. Conclusions: Organizing studies addressing the prevention and treatment needs of TDIs and educational programs aimed toward parents and school teachers are of paramount importance. Furthermore, recognizing the tremendous treatment negligence is extremely critical to adequately analyze indifference of the people toward dental trauma and its consequences.